VEGFR2 pY949 signalling regulates adherens junction integrity and metastatic spread - Xiujuan Li (Nature Portfolio, 2016)
Signals through VEGF receptor 2 (VEGFR2) increase vascular permeability, promoting cancer progression. Here the authors show that a point mutation in VEGFR2 preventing its auto-phosphorylation leads to reduced metastatic spread and improved response to chemotherapy in tumor-bearing mice, without affecting tumor inflammation.